Effective Micro-organisms for Mosquito Larva Control : Community Participation - Mongkonchaipanit, Chutikan (Journal of Health Science of Thailand, 2017)
In mosquito larvae control, many methods, including chemical and non-chemical, are used. The most frequently used methods is temephos or Abate®, with negative consequences such as its smell, cost and larvae resistance in a long run. The sporadic outbreaks of dengue hemorrhagic fever in Kamphaeng subdistric during 2004-2007 were one of major health threats even with active control efforts. The larvae index remained high and cost on chemical control (Abate®) climbed up. In 2008 an outbreak of dengue hemorrhagic fever was expected. The health partnership in Kamphaeng subdistric were activated and in brainstorming sessions to find more appropriate solutions on replacing Abate® by effective micro-organisms (EM). The raw materials of EM for control mosquito larvae included clay, soft rice bran and red sugar. The larval mortality were then investigated and compared between those of EM and Abate®. In laboratory the EM killed larvae within 30 minutes, in 3 hours the mortality rate for EM and Abate® became 76.6 percent and 66.7 percent, respectively. Once the EM product were tested under field conditions in 20 households, within 3 hours, the mortality rate were complete and mosquito larvae disappeared through the next month. The use of EM product was effective in continuous mosquito larvae control, in the field and in laboratory. The cost of EM production was 32 bath, it can be 3 time diluted and still effective and safely used as fertilizer for organic vegetable farming. The next improvement of this product is to dehydrate and concentrate it, forming a clump to accommodate its distribution and use.